Educational Context Diagnosis: Analyzing the Educational Dimension - Juca-Aulestia José Marcelo; Cabrera-Paucar , Edwin José; Iriarte-Solano, Margoth (Journal of Ecohumanism, 2025)
This research examines the impact of the school environment on instruction and knowledge acquisition, emphasizing the need for a comprehensive methodology that addresses instructional, technological and social implications; including teaching methods, learning materials and plans, evaluation, school culture, and teacher training. The findings indicate that teachers generally perceive their work positively, though discrepancies arise in how educational actors evaluate these perceptions. Additionally, there is a disconnect between technological integration in the classroom and the curriculum’s demands, as well as family expectations, challenges in school culture and teacher training require further attention. It can be concluded that strengthening inclusive evaluation, improving teacher training, and expanding access to technology are crucial steps toward enhancing educational excellence and its social relevance, thereby promoting equity and alignment with modern demands.